962: Al-Maqqarī on the Oath of Allegiance Given by the Rulers of León to al-Ḥakam II (Transmediterranean History, 2023)
The Islamic oath of allegiance (bayʿa) is traditionally regarded as a political tool that formalises a relationship of dependency between a Muslim ruler and his Muslim subjects. This article discusses a case from fourth/tenth-century al-Andalus, in which the bayʿa is used to formalise a relationship of dependency between the Umayyad caliphate of Córdoba and different representatives of the kingdom of León. It shows that this extraordinary use of a tool of internal policy in a foreign policy context can be explained against the backdrop of the Umayyad caliphate’s strategy in North Africa. There, it tried to gain a foothold by employing the same measures used vis-à-vis the kingdom of León.
Keywords: al-Andalus; Córdoba; León; Umayyads; Iberian Peninsula; diplomacy; oath of allegiance; North Africa; treaty; dependence; Christians under Muslim rule; interpreters